Do Gender Norms Become Less Traditional with Displacement? The Case of Colombia - Rubiano-Matulevich, Eliana (World Bank, Washington, DC, 2021)
Conflict-induced displacement is associated with loss of human and physical capital and psychological trauma. Households and social structures that produce and reproduce gender norms are disrupted, providing opportunities for change. This paper operationalizes a definition of gender norms that brings together the behaviors and attitudes of displaced and non-displaced women using household survey data for Colombia. The results of a two-step estimation involving kernel-based propensity score matching and multilevel linear regression models show that gender norms condoning violence against women relax with displacement, while those that limit women’s economic opportunities become more rigid. The findings also reveal a misalignment between attitudes and behaviors in other domains. Displaced women have less rigid patriarchal attitudes, but their ability to decide about contraception and their own earnings decreases following displacement.